2010
DOI: 10.1111/j.1750-3841.2010.01737.x
|View full text |Cite
|
Sign up to set email alerts
|

Trans Fatty Acids Content and Fatty Acid Profiles in the Selected Food Products from Korea between 2005 and 2008

Abstract: Since a high intake of trans fatty acids (TFA) has been associated with the increased risk of developing cardiovascular disease, food regulation worldwide has been amended with respect to nutrition labeling and health claims on TFA. In the present study, the TFA levels of Korean food products were investigated to assess the regulation effect of TFA labeling. Same Korean food products within 7 different categories were purchased in years 2005 and 2008, and the contents of TFA and lipid and fatty acid compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
(17 reference statements)
1
14
0
Order By: Relevance
“…Although all of the studies that reported on the different FAs in products pre– and post–policy interventions found reductions in TFA amounts in foods, there were mixed findings in terms of SFA amounts in foods. Seven studies included information on MUFA and PUFA contents in foods ( 18 20 , 22 , 28 , 29 , 31 ), 6 of which found increases in either MUFAs or PUFAs (or both). Moreover, 12 studies examined the combined TFA and SFA contents of foods before and after the introduction of a TFA policy, with all but one study ( 22 ) reporting a reduction post–policy intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Although all of the studies that reported on the different FAs in products pre– and post–policy interventions found reductions in TFA amounts in foods, there were mixed findings in terms of SFA amounts in foods. Seven studies included information on MUFA and PUFA contents in foods ( 18 20 , 22 , 28 , 29 , 31 ), 6 of which found increases in either MUFAs or PUFAs (or both). Moreover, 12 studies examined the combined TFA and SFA contents of foods before and after the introduction of a TFA policy, with all but one study ( 22 ) reporting a reduction post–policy intervention.…”
Section: Resultsmentioning
confidence: 99%
“…There has been consistent evidence that a mandatory or widely implemented labeling of foods has an effect through food reformulation. The adoption of the Choices logo in the Netherlands (25), the mandatory trans fat labeling in South Korea (26), and the Pick the Tick logo in New Zealand (27) has led, in each instance, to improvements in the nutrient profile of food products on the market. Thus, the main mechanism through which labels work to affect the diets of populations may be by creating an incentive for food manufacturers to improve the nutritional profile of their products.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies evaluated intakes of specific products or meals as outcomes, rather than longterm (habitual) intakes. About half were performed in general community, 45,52,53,[55][56][57][58]61,[71][72][73][74][75][76][77][78][79][80][81]84,85,[90][91][92][93]97,98,101,[103][104][105][106] and half in universities/ schools 49,54,59,60,[62][63][64]70,83,88,89,99,100,102 or hospitals/other worksites 50,51,[65][66]…”
Section: Evidence Synthesis Study Characteristicsmentioning
confidence: 99%